2020
DOI: 10.1371/journal.pone.0238080
|View full text |Cite
|
Sign up to set email alerts
|

Long-term multimodal imaging in acute posterior multifocal placoid pigment epitheliopathy and association with coxsackievirus exposure

Abstract: The purpose of this study was to evaluate potential insights into the pathogenesis of acute posterior multifocal placoid pigment epitheliopathy (APMPPE) using multimodal diagnostic imaging and laboratory evaluation in long-term follow-up. A retrospective, single-center case series was conducted on seven consecutive patients (14 eyes) who were given a diagnosis of APMPPE from March 1, 2011, through June 30, 2019 with at least three months of follow-up. Clinical characteristics (age, symptoms, visual acuity [VA]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Acute idiopathic maculopathy is a rare, self-limited, macular disease disproportionately affecting young men [ 1 ]. It has been postulated that AIM exists on a spectrum of acute multifocal placoid pigment epitheliopathy (APMPPE) [ 5 ] and our case illustrates this point. The lesions in APMPPE clinically appear yellow-white and may have a complex outer boundary due to confluence of smaller lesions.…”
Section: Discussionsupporting
confidence: 67%
“…Acute idiopathic maculopathy is a rare, self-limited, macular disease disproportionately affecting young men [ 1 ]. It has been postulated that AIM exists on a spectrum of acute multifocal placoid pigment epitheliopathy (APMPPE) [ 5 ] and our case illustrates this point. The lesions in APMPPE clinically appear yellow-white and may have a complex outer boundary due to confluence of smaller lesions.…”
Section: Discussionsupporting
confidence: 67%
“…Its cause has not been clearly elucidated yet since the incidence of these syndromes is very low. However, Coxsackie antibody titers in acute and treated cases seem to correlate in some series [16].…”
Section: Discussionmentioning
confidence: 95%
“…Using multimodal imaging in APMPPE, some authors have found choroidal inflammation as a preceding and necessary factor for RPE, and subsequent damage in cones [16]. This choroidal inflammation may be generated solely by the entry of SARS-CoV-2 via the angiotensin-converting enzyme 2 receptor (ACE) in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…APMPPE lesions show initial hypoautofluorescence corresponding to the hyper-reflectance of the outer retinal layers on SD-OCT, likely secondary to its masking effect (Fig. 3 A) [55]. A progressive increase in hyperautofluorescence is observed later on in the course of the disease when outer retinal findings progress to disruption of the RPE layer, with a mixed pattern of hypoautofluorescence and hyperautofluorescence (Fig.…”
Section: Fundus Autofluorescencementioning
confidence: 96%
“…A progressive increase in hyperautofluorescence is observed later on in the course of the disease when outer retinal findings progress to disruption of the RPE layer, with a mixed pattern of hypoautofluorescence and hyperautofluorescence (Fig. 3 B) [55,56]. Later in the disease course, a more homogenous hypoautofluorescent pattern suggesting focal areas of photoreceptors/RPE atrophy might develop [55,56].…”
Section: Fundus Autofluorescencementioning
confidence: 96%